2021
DOI: 10.1097/qad.0000000000002887
|View full text |Cite
|
Sign up to set email alerts
|

Global estimates for the lifetime cost of managing HIV

Abstract: We conducted a systematic review (PROSPERO:CRD42020184490) using five databases from 1999-2019. Methods:Studies were included if they reported primary data on lifetime costs for people living with HIV. Two reviewers independently assessed the titles and abstracts, and data were extracted from full texts: lifetime cost, year of currency, country of currency, discount rate, time horizon, perspective, method used to estimate cost, and cost items included. Descriptive statistics were used to summarize the discount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
(98 reference statements)
1
12
0
Order By: Relevance
“…This study adds to the global body of literature on estimating the lifetime cost of HIV management, providing a comparison to lifetime cost estimates in other countries and a reference for future Australian lifetime cost models for healthcare budgeting. 10 We also add to the international literature by underscoring the relatively high contribution of the cost of ART and thus the potential costsavings from using generic drugs. When multiplying the lifetime cost estimate by the estimated number of PLHIV in Australia (for the Australian population of PLHIV at the start of 2019), it would cost the government an estimated A $7.9 billion over the next 61 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adds to the global body of literature on estimating the lifetime cost of HIV management, providing a comparison to lifetime cost estimates in other countries and a reference for future Australian lifetime cost models for healthcare budgeting. 10 We also add to the international literature by underscoring the relatively high contribution of the cost of ART and thus the potential costsavings from using generic drugs. When multiplying the lifetime cost estimate by the estimated number of PLHIV in Australia (for the Australian population of PLHIV at the start of 2019), it would cost the government an estimated A $7.9 billion over the next 61 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, only two estimates of the lifetime cost of HIV management in Australian adults have been published. 10 Gray et al estimated a lifetime cost of A$424 844 (discounted at 3.5%, 2015 A$), 11 and the study by Tilden et al reported a lifetime cost of A$146 300 (discounted at 5%, 2010 A$). 12 However, since the publication of these two estimates, Australia has made changes related to commonly used antiretroviral regimens (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these obstacles, new global initiatives for HIV prevention are required to tackle the challenges and worldwide financial burden of this epidemic [157]. Ideally, a prophylactic HIV vaccine would be available, enabling global vaccination campaigns in the near future.…”
Section: Ccr5 Antagonistsmentioning
confidence: 99%
“…In a high income country like Australia, the additional cost of providing universally subsidised PrEP care would likely be lower than treating preventable new HIV infections, with an estimated lifetime cost of more than US$350 000 per HIV infection diagnosis. 6 …”
Section: Demographic Characteristics Immunodeficiency Virus (Hiv) Acq...mentioning
confidence: 99%